2000
DOI: 10.1017/s0022377800008849
|View full text |Cite
|
Sign up to set email alerts
|

On resistive magnetohydrodynamic equilibria of an axisymmetric toroidal plasma with flow

Abstract: It is shown that the magnetohydrodynamic equilibrium states of an axisymmetric toroidal plasma with finite resistivity and flows parallel to the magnetic field are governed by a second-order partial differential equation for the poloidal magnetic flux function ψ coupled with a Bernoulli type equation for the plasma density (which are identical in form to the corresponding ideal MHD equilibrium equations) along with the relation ∆ ⋆ ψ = V c σ. (Here, ∆ ⋆ is the Grad-Schlüter-Shafranov operator, σ is the conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…This is equivalent to equation (28) in the single fluid limit under the replacement B 2 = |∇ | 2 + (B φ R) 2 using equation 9, substitution for v using equation (10) and v φ using equation (12). Correcting for transcription errors in Guazzotto et al 2 , the transformed Grad-Shafranov equation of Guazzotto et al (equation (19a) in [14]) reads…”
Section: A Multi-fluid Mhd Equilibrium Model For Tokamaksmentioning
confidence: 99%
See 1 more Smart Citation
“…This is equivalent to equation (28) in the single fluid limit under the replacement B 2 = |∇ | 2 + (B φ R) 2 using equation 9, substitution for v using equation (10) and v φ using equation (12). Correcting for transcription errors in Guazzotto et al 2 , the transformed Grad-Shafranov equation of Guazzotto et al (equation (19a) in [14]) reads…”
Section: A Multi-fluid Mhd Equilibrium Model For Tokamaksmentioning
confidence: 99%
“…To help solve the multi-fluid model in realistic configurations, we draw on the extensive body of literature for solving tokamak MHD equilibria with flow (see [6][7][8][9][10][11][12] and references therein). Two recent examples which largely shape our work are McClements and Thyagaraja [13] and Guazzotto et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…To enable quasi-steady and sustainable electric fields with field-aligned flows, it is necessary to simultaneously solve the resistive Ohm's law and the momentum equation. This was first investigated by Grad & Hogan 1970 and subsequently by Throumoulopoulos (1998) and Throumoulopoulos & Tasso (2000) for the case of axisymmetric fields. These authors found several classes of analytical equilibria with physically plausible σ = 1/η profiles, stating clearly that in general, fields with constant resistivity do not exist by proving that only the assumption of a spatially varying σ makes the equilibrium problem well posed.…”
Section: Derivation Of the Mhd Modelmentioning
confidence: 99%
“…In 2D, the search of the Poincaré class of the total electric field is linked to the Poincaré class of the resistivity. It is well known that for exact and analytical reconnection solutions, it is not sufficient to assume any non-ideal term or non-idealness or for example a constant resistivity (Priest et al 1994;Craig & Henton 1995;Watson & Craig 1998;Throumoulopoulos & Tasso 2000;Titov & Hornig 2000;Nickeler et al 2012Nickeler et al , 2014. For the classical role of reconnection in 2D it is inevitable that the plasma flow can cross both magnetic separatrix branches, as this scenario constitutes the reconnection solution.…”
Section: Introductionmentioning
confidence: 99%